Numerical analysis of the effects of changing hydraulic parameters on saltwater intrusion in coastal aquifers. Issue 8 (7th November 2016) - Abd-Elaty, Ismail; Abd Elhamid, Hany Farhat; Javadi, Akbar
Abstract : Purpose: The purpose of this paper is to develop and validate a numerical model to study the effect of changing hydraulic parameters on saltwater intrusion in coastal aquifers. Design/methodology/approach: The numerical model SEAWAT is validated and applied to a hypothetical case (Henry problem) and a real case study (Biscayne aquifer, Florida, USA) for different values of hydraulic parameters including; hydraulic conductivity, porosity, dispersion, diffusion, fluid density and solute concentration. The dimensional analysis technique is used to correlate these parameters with the intrusion length. Findings: The results show that the hydraulic parameters have a clear effect on saltwater intrusion as they increase the intrusion in some cases and decrease it in some other cases. The results indicate that changing hydraulic parameters may be used as a control method to protect coastal aquifers from saltwater intrusion. Practical implications: The results of the application of the model to the Biscayne aquifer in Florida showed that the intrusion can be reduced to 50 percent when the hydraulic conductivity is reduced to 50 percent. Decreasing hydraulic conductivity by injecting some relatively cheap materials such as bentonite can help to reduce the intrusion of saltwater. So the saltwater intrusion can be reduced with relatively low cost through changing some hydraulic parameters. Originality/value: A relationship to calculate intrusion length in coastal aquifer is developed and the impact of different hydraulic parameters on saltwater intrusion is highlighted. Control of saltwater intrusion using relatively cheap method is presented.